Metabolism of very low density lipoproteins after cessation of cholesterol feeding in rabbits. A factor potentially contributing to the slow regression of atheromatous plaques. - Daugherty, A (1986)
Aortic atheromatous plaques regress slowly in cholesterol-fed rabbits that have been returned to normal laboratory diet. To delineate metabolic factors potentially responsible for persistence of atherosclerosis under these conditions, the physical, chemical, and metabolic characteristics were determined for lipoproteins of d less than 1.006 g/ml; such lipoproteins are thought to be the major determinant of progression of atherosclerotic lesions in cholesterol-fed rabbits. At the time of return to a normal laboratory diet regimen after 3 mo of feeding with cholesterol-enriched laboratory diet, plasma cholesterol concentrations were 2,275 +/- 252 mg/dl, mostly attributable to cholesteryl ester-rich very low density lipoproteins (VLDL). On the hypercholesterolemic diet, fractional catabolic rates of plasma clearance of 125I-labeled VLDL were reduced (0.011 +/- 0.002 vs. 0.151 +/- 0.015 h-1), but the total VLDL catabolic rate was increased considerably (17.1 +/- 2.2 vs. less than 1.2 +/- 0.4 mg of protein/kg X d), because of the expansion of the endogenous pool of cholesteryl ester-rich VLDL. The total catabolic rate of VLDL was maintained above estimated control values (5.8 +/- 0.7 mg protein/kg X d) even 10 wk after return of the rabbits to a normal chow regimen, an effect attributable to continued high rates of cholesteryl ester-rich VLDL synthesis in liver. Accumulation of cholesteryl ester-rich VLDL into aortic tissue persisted at a high rate. Thus the persistence of aortic atheromatous lesions after cessation of cholesterol feeding was attributable in part to continued high rates of hepatic production of cholesteryl ester-rich VLDL and its persistent delivery into the aortic wall.